Consuming Nostalgia on Facebook - Caliandro, Alessandro; Gandini, Alessandro; Bainotti, Lucia; Anselmi, Guido (The Platformisation of Consumer Culture, 2024)
Building on the notion of "consumer nostalgia," in this chapter we explore how nostalgia is represented on Facebook through consumer goods, and how Facebook structures and fosters the circulation of a nostalgic imaginary. Based on the analysis of 63 Facebook Pages dedicated to the 1980s, we show that nostalgia on the Facebook platform does not emerge as an undistinguished magma, but rather finds expression around particular consumption objects from the '80s (e.g. ads, cartoons, TV shows, etc.), which allow users to deploy (and position themselves around) specific grammars and vernaculars. Despite the increasing importance of experience and access-based consumption in digital environments, a peculiar feature of the imaginary of nostalgia on Facebook turns out to be the persistence of references to material consumer goods.